Frequency, dispersion, association, and keyness : revising and tupleizing corpus-linguistic measures - Gries, Stefan Thomas, 1970- (Studies in corpus linguistics ;, 2024)
"This book is an attempt to revisit the main specifically corpus-linguistic statistics/measures the field has been relying on for decades: frequency, dispersion, association, and keyness. The book first discusses the purpose of these measures and how these have been measured. Then, the book makes three main proposals: First, that many measures of dispersion, association, and keyness are too confounded with frequency and how to 'take frequency out of them' to obtain conceptually cleaner / more interpretable measures. Second, that many existing measures can be replaced by the simple information-theoretic measure of the Kullback-Leibler divergence and that it, too, can have frequency 'removed' from it. Third, that corpus linguistics should abandon the tradition of trying to describe our findings with a single number and adopt a tupleization approach instead, where we use several separate dimensions of information for description and interpretation. The book is written in an informal, hands-on style and comes with its own R package featuring functions, example data, and several thousand lines of code exemplifying all applications"